2022
DOI: 10.3390/en15082924
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics on the Basis of the Frequency-Temperature Dependences of the Loss Angle Tangent of Heavily Moistured Oil-Impregnated Pressboard

Abstract: The aim of this study was to perform precision measurements of the frequency-temperature dependences of the loss angle tangent of the liquid-solid composite with the FDS Dirana meter. The composite consisted of heavily moistered oil-impregnated pressboard. The moisturization of the pressboard occurred in a manner as close as possible to the process of wetting the insulation in power transformers to a moisture content of (5.0 ± 0.2) wt. %. This value of moisture content was chosen because exceeding this value c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Firstly, a precise determination of the so-called model characteristics-the frequency-temperature dependencies of the oil-impregnated pressboard moistened to a given water content-must be carried out. In a previous study [28], model characteristics were determined for water contents ranging from 1 wt.% to 4 wt.% while model characteristics were determined for a critical content of 5 wt.% in the papers [29][30][31][32]. Secondly, transformer insulation measurements should be carried out under conditions of thermodynamic equilibrium between the pressboard, insulation oil and water [5,33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, a precise determination of the so-called model characteristics-the frequency-temperature dependencies of the oil-impregnated pressboard moistened to a given water content-must be carried out. In a previous study [28], model characteristics were determined for water contents ranging from 1 wt.% to 4 wt.% while model characteristics were determined for a critical content of 5 wt.% in the papers [29][30][31][32]. Secondly, transformer insulation measurements should be carried out under conditions of thermodynamic equilibrium between the pressboard, insulation oil and water [5,33].…”
Section: Introductionmentioning
confidence: 99%
“…This means that determining the insulation reliability status of transformers based on software dedicated to FDS meters does not accurately detect the risk of failure. In [31], it was found that in order to match the frequency dependence of the loss angle tangent simulated by the meter to the waveform obtained by measurement, a temperature, greater than the actual measurement temperature, must be entered into the software. Even after manual temperature correction, the result given by the meter is overestimated by approximately 1 wt.% in relation to the actual moisture content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, pressboard plates were moistened to various moisture contents, impregnated with mineral oil, and then temperature-frequency characteristics were determined [24][25][26][27]. Recent publications [28,29], have determined that FDS meter software provides moisture values inconsistent with actual ones. This implies that the models assumed in the meter software do not consider the real phenomena of conductivity and dielectric relaxation occurring in transformer insulation.…”
Section: Introductionmentioning
confidence: 99%